دراسة التجانس المصلي لبعض ذراري فيروس التهاب الجراب المعدي المعزولة من دجاج اللحم(الفرّوج) في منطقة الساحل السوري - عبد العزيز فهيم (Latakia University Journal -Biological Sciences Series, 2019)
تم عزل وتصنيف خمس ذراري لفيروس التهاب الجراب المعدي (, NK-94, BZ-93 95 BKH-,SA-95 MR-96 ) من الطيور المريضة والنافقة بالمرض عند انتشار الإصابات الحقلية في مزارع إنتاج الفرُّوج، ودرست بعض خصائصها الحيوية والمناعية في أبحاث سابقة [3,15,22]. أثبت البحث وجود التجانس المصلي بين ذراري الفيروسات المعزولة (, NK-94, BZ-93 95 BKH-,SA-95 MR-96 ) في اختبار الترسيب في الغراء الهلامي بنتيجة التفاعلات التصالبية لمستضدات الذراري وأضداد كل منها. تأكد تواجد واستمرار العدوى ودوران فيروس حقلي ممرض من نمط مصلي متجانس في مزارع رعاية الفرّوج المنتشرة في مناطق مختلفة من الساحل السوري. Isolation and the classification of five strains of the infectious bursal disease virus (BZ 93, NK- 94, BKH-95, SA- 95, MR- 96 ) from sick and deceased birds was achieved when the infection spread in broiler farms, while some of its biological and immunological characteristics have been already investigated in previous researches [3,15,22] Serological homogeny was proved between the isolated strains(BZ 93, NK- 94, BKH-95, SA- 95, MR- 96 ) as a result of cross tests in the Agar gel precipitation test (AGPT). Circulation of the pathogens virus of fields from the same type in the broiler farms in different locations of the coastal region of Syria was confirmed.